Using habitat to quantify ecological effects of restoration and water management alternatives. (August 2015) - Hickey, John T.; Huff, Rochelle; Dunn, Christopher N.
Abstract: The Ecosystem Functions Model (HEC-EFM) is designed to help study teams determine ecosystem responses to changes in the flow regime of a river or connected wetland. HEC-EFM analyses involve: 1) statistical analyses of relationships between hydrology and ecology, 2) hydraulic modeling, and 3) use of Geographic Information Systems (GIS). Through this process, study teams define existing ecologic conditions, highlight promising restoration sites, and assess alternatives according to predicted ecosystem changes. HEC-EFM has many strengths, most notably it 1) is capable of testing change for many ecological relationships and management scenarios, 2) links ecology with established hydrologic, hydraulic, and GIS tools, and 3) can be applied quickly, inexpensively, and can incorporate expert knowledge. This paper introduces HEC-EFM and describes its use for statistical analyses and habitat mapping. Two examples are provided: Provision of Sacramento splittail minnow spawning habitat, San Joaquin River, California, USA, and cottonwood seedling establishment, Bill Williams River, Arizona, USA. Highlights: The Ecosystem Functions Model predicts ecological responses to changes in hydrology. Links ecology with established hydrologic, hydraulic, and GIS tools for decision support. Quick, inexpensive means to incorporate expert knowledge and build ecologic models. Key output include eco-performance measures and habitat maps for management alternatives. Software described are applicable to a wide range of ecosystems and management concerns.